Solitary Rectal Ulcer Syndrome in a Teenage Girl: A Case Report - Nahid, Khan Lamia; Md Rukunuzzaman, -; Md Benzamin, -; Begum, Fahmida; Karim, ASM Bazlul (Dhaka Shishu (Children) Hospital Journal, 2021)
Abstract not available DS (Child) H J 2020; 36(1) : 67-70